Shifting Indigenous House Values in Local Communities - Ngarawula, Bonaventura; Sontoe (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to examine the shifting values of traditional houses in the Ngaju Dayak Community in TumbangKurik Village, Kahayan Hulu Utara District, Gunung Mas Regency, Central Kalimantan Province. This study used a qualitative approach to the case study method. This method was directed at the object, which was the head of the family who lived in a Betang house in the TumbangKurik village. The research location was concentrated in the TumbangKurik village, Kahayan Hulu Utara District, Gunung Mas Regency. Sources of information and sources in this study are: (1) the chieftains; (2) intellectual figures: (3) Religious figures: (4) Local government. While non-human sources of information are documents, notes, and files related to the social interaction of the Ngaju Dayak community in TumbangKurik Village, Gunung Mas Regency. Data collection techniques are observation, interview, and documentation. Data analysis techniques follow the theory of Strauss & Corbin: opening coding, axial coding, and selective coding. Based on the results of the study, researchers determined that: (1). Betang Traditional House contains cultural values that historically became a reference and guide to the life of the Ngaju Dayak community in facing the development and shifting of local cultural values. (2). Betang Traditional House has an important function for the life of the Ngaju Dayak community as an image of the Dayak community, which has a strong culture. (3). Ngaju Dayak Betang House in TumbangKurik Village has a central pillar and front door that symbolizes the life of the Dayak people as a unifying medium of the Dayak community where expressive symbols can help understand changes in their interactions. (4). "BelomBahadat," with the principles of BatangGaring and DadangTingang, is a source of life inspiration and a way of life for inculcating cultural values of the Ngaju Dayak community. This study recommends further research on the local wisdom of the Dayak people.